FEM Analysis of Stress Distribution in the Hermetic Harmonic Drive Flexspline - Pacana, J.; Witkowski, W.; Mucha, J. (Проблемы прочности, 2017)
The paper deals with the numerical stress calculation in the flexspline tooth rim of the harmonic drive. Due to the complex geometry of the toothed ring in the flexspline, the teeth were modeled as a ring, which height corresponded to the particular stress concentration in the teeth. To study the effect of type of wave generator on the stress distribution in the flexspline, the following models were elaborated: two-roller, four-roller, cam, and disk. The stress calculations were performed for the two cases: a zero torque load and the torque load value, corresponding to the true operation conditions of the hermetic harmonic driv